Usability and motivational impact of a fast-paced immersive virtual-reality lecture on international middle-school students in geoscience education - A. Zulhilmi; Y. S. Hayakawa; D. R. Newman (Geoscience Communication)
Immersive virtual reality (VR) offers educators an innovative tool to teach geoscience, addressing challenges in conveying the Earth's 3D characteristics, which have traditionally been taught through field visits and experiences that are often inaccessible to many due to socioeconomic, political, and logistical barriers. VR provides an alternative experience, allowing users to virtually explore geological sites beyond physical and situational constraints. Despite its potential, the implementation of geoscience-focused VR lectures remains largely unexplored. As a pioneering case study, this research investigates the usability and motivational impact of VR by developing a fast-paced virtual reality lecture on landslides for middle-school students. Approximately 60 students from diverse cultural and educational backgrounds participated. Results revealed that the VR lecture was usable, with key strengths being its ability to engage students and deliver satisfaction. Compared to traditional (lecture and hands-on) teaching methods, VR excelled in fostering interest, enjoyment, and perceived choice. This study provides valuable insights into the practical implementation of VR in geoscience education, demonstrating its potential to make geoscience topics more accessible and engaging for diverse student groups. Future research should explore strategies to address usability challenges and enhance the motivational attributes of VR, paving the way for its broader adoption in geoscience educational settings.